Nanostructures synthesized by the reverse microemulsion method and their magnetic properties. (7th October 2020) - Das, Anirban; Natarajan, Kalithasan; Tiwari, Shalini; Ganguli, Ashok Kumar
Abstract: The reverse microemulsion (ME) based synthesis is a versatile route for obtaining a variety of nanomaterials with controlled size and shape. Optimization of the various components involved in the formation of a ME is necessary to obtain the desired morphology and size. Magnetic materials have great significance in various fields like data storage, biomedical imaging, therapeutics, catalysis and sensor applications to name a few. It is seen that the magnetic properties of the nanostructures synthesized by ME methods are distinct from the structures obtained by other methods. Further, even for the nanostructures synthesized by the ME method, the magnetic properties depend upon their size and morphology. Thus, tuning the size and morphology of the nanostructures to tailor the magnetic properties is a desirable objective of several research projects. This mini-review comprehensively discusses those nanostructures synthesized by the ME method whose magnetic properties were investigated.